Implementing and Evaluating Growth Mindset Pedagogy – A Study of Finnish Elementary School Teachers - Rissanen, Inkeri; Laine, Sonja; Puusepp, Ita; Kuusisto, Elina; Tirri, Kirsi (Frontiers in Education, 2021)
This article presents a study of five teachers at a Finnish elementary school who implemented and evaluated growth mindset pedagogy (GMP). The teachers received GMP training and conducted student interventions in their classrooms. We analyzed the impact of GMP on the teacher’s pedagogical thinking and practices and found significant differences between fixed-mindset and growth-mindset teachers in the ways they internalized and applied GMP principles. The most important value of GMP was seen in its impact on emotion regulation through the normalization of hardship in learning. We discuss the dangers of a superficial understanding of growth mindsets in education.